Impact of Municipal Political Decision Makers’ Turnover on the Degree of Building and Land Use in China: an Empirical Study Based on the Profiles of the Secretaries of Municipal Party Committees - Chengzhi Yin; Hao Sun (Transylvanian Review of Administrative Sciences, 2019)
China’s rapid urbanisation in the past 30 years has been a prominent issue all over the world. Few studies have elaborated the urbanization in China, especially the overly speedy building intensity growth in contemporary China from the perspective of local decision makers. This study aims to explain the local decision-making driving force of the rapid growth of the degree of building and land use by analysing the interaction between local decision makers’ turnover and the degree of building and land use. The Secretaries of Municipal Party Committees (SMPCs) have been selected as the representatives of the decision makers of Chinese local governments while the newly increased floor area has been selected as an indicator of the degree of building and land use. On the basis of the panel data of 35 large- and medium-sized Chinese cities from 2000 to 2014, Stata 14.0 has been applied to implement a regression analysis. The research findings show that any turnover of the Secretaries of Municipal Party Committees (SMPCs) may create new floor area. The causal mechanisms hypotheses have also been proven. Generally, the SMPCs are motivated by a need to promote urban growth, and especially, when the SMPCs hold power by the same-ranking lateral transferring or same-ranking vertical dispatch in the municipality, its floor area is more likely to increase. Furthermore, the more the floor area increases, the greater the possibility of promotion will get. These findings could be an explanation for China’s high-speed spatial urbanization from a public administration point of view and a practical understanding of the Chinese decision-making mechanism in urban development.